Disseminating the Research Output of Major Indian R & D Organization’s through Open Access Institutional Repositories: Challenges and Opportunities - Barve, Sunita; Naika, Manju (Journal of Information and Knowledge, 2020)
This study examines the implementation status of institutional repositories (IRs) in Council of Scientific and Industrial Research (CSIR) laboratories. It assesses the level at which CSIR laboratories have updated their publications in IRs to facilitate open access to scholarly publications. The paper discusses the challenges faced by CSIR IRs in maintaining open access and updating content regularly. It identifies publications indexed in the WoS database and also discusses the open access initiatives at CSIR labs. The study suggests an effective strategy for successfully implementing IRs and covering the entire set of publications of CSIR laboratories.